Legal Protection for Journalists in Defamation Cases - Billy Valentino Pihawianu Sinulingga; Yurika Fahliany Dewi; Hilyatul Asfia (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze legal protection for journalists in Indonesia by reviewing the normative conflict between the Information and Electronic Transactions (ITE) Law and the Press Law, using the Palangka Raya District Court Decision Number 108/Pid.Sus/2019/PN Plk as a case study. The study employs a normative juridical method with a library research approach, examining legislation, court decisions, and relevant literature. The findings indicate the presence of a normative conflict between the Press Law, which provides dispute resolution mechanisms through the right of reply and mediation by the Press Council, and the ITE Law, which prescribes imprisonment of up to four years for defamation. Data show that fourteen journalists were reported under the ITE Law during the 2019–2021 period due to inconsistent understanding among law enforcement officials, weak implementation of the Memorandum of Understanding (MoU) between the National Police and the Press Council, and subjective interpretation of the element “without rights” under the ITE Law. The acquittal of journalist Yundhi Satrya Siman applied the legal principle of lex specialis derogat legi generali, prioritizing the Press Law as the applicable special regulation. The study formulates criteria for distinguishing protected journalistic activities, which include actions conducted by registered journalists, adherence to the journalistic code of ethics, orientation toward the public interest, and publication through an authorized press company.